Eksplorasi teks sastra frankofon dalam pengajaran bahasa Prancis sebagai bahasa asing di Indonesia - Intan, Tania; Mulyadi, Yadi (Universitas Pendidikan Indonesia, 2021)
The term francophone refers to the French-speaking community around the world, whereas francophone literature is all French-language texts produced by authors originating from francophone countries. This study discusses the exploration of the literary text of the francophones in teaching French as a foreign language in Indonesian context. The method used is the descriptive qualitative literature review approach. Data in the form of words, phrases, and sentences in French were collected from data sources, which consisted of French language teaching manuals and francophones novels. Data translated directly by researchers and validated by native French speakers. The data are then classified, interpreted, and reviewed according to the context. The results of this study indicate that: through reflection in a pedagogical framework, it can be agreed that the literary text of the francophones, like other literary texts from around the world, is fertile ground for building learners' intercultural competence. From the discussion, it is also known that the text of the francophones has been used in FLE learning in Indonesia although it is not yet optimal, because it is limited by the linguistic competence of the learner and has only been given to classes from middle to the upper level (between levels B1-B2). This study also proves that the literary text of the francophones can be attributed as a potential learning medium to be explored in the language class, but it requires certain competencies from the teacher, adequate preparation, and thorough execution.